Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Pada Mata Pelajaran Informatika Kelas X di SMK Negeri 1 Solok Selatan - Mutiara, Devita; Irsyadunas, Irsyadunas; Junaidi, Satrio (Jurnal Informatika, 2023)
The obstacle encountered in the subject of informatics, specifically in the topic of operating systems, is the lack of interactive learning media that support students' learning outcomes. As a result, students find it challenging to grasp the material during their studies. This research aims to develop a valid and practical multimedia-based interactive learning media. The research employs the Research and Development (R&D) method with the MDLC (Multimedia Development Life Cycle) development model. The study involves a sample of 29 students as subjects. Data collection is conducted through a Likert-scale questionnaire. The data analysis technique for the development of multimedia-based interactive learning media using Adobe Animate CC is quantitative data analysis. The findings of the research reveal that the average validity score from the validation conducted by media experts is 0.82 with a valid category. Similarly, the validity score from the validation by subject matter experts is 0.89 with a valid category. In the practicality test, the feedback from teachers yielded a result of 94.09% with a highly practical category, and the feedback from students resulted in a score of 85.10% with a highly practical category. Based on the assessment and input from media and subject matter experts, as well as the results of field trials, it can be concluded that this multimedia-based interactive learning media has undergone a thorough feasibility test and is suitable for use as an informatics teaching tool.